2014
DOI: 10.1108/pijpsm-06-2011-0057
|View full text |Cite
|
Sign up to set email alerts
|

Police students’ social background, attitudes and career plans

Abstract: Purpose: To compare the social background of Norwegian and Swedish police students. Are there differences in the students' social background, and if so, are such differences reflected in different attitudes and career plans among the students?Design/methodology/approach: The questions are explored on the basis of survey data on all Norwegian and Swedish police students who started their education in 2009 (N=737). The methods employed are cross-tabular analysis and multivariate linear regression. Findings:The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…At the beginning of a career in policing, recruit levels of pride in the job, work commitment, and empathy for others are often at their highest level (Bringsrud Fekjaer, 2014). The results from this survey reflect this finding as most of the recruits have high levels of integrity, high levels of pride in their work, and a positive commitment to policing.…”
Section: Discussionsupporting
confidence: 57%
“…At the beginning of a career in policing, recruit levels of pride in the job, work commitment, and empathy for others are often at their highest level (Bringsrud Fekjaer, 2014). The results from this survey reflect this finding as most of the recruits have high levels of integrity, high levels of pride in their work, and a positive commitment to policing.…”
Section: Discussionsupporting
confidence: 57%
“…Among the highly cited police researchers we also find examples of quantitative police research, such as Strömwall and Granhag (2003) and Glomseth, Gottschalk, and Solli-Saether (2007). Other examples of quantitative police research can be found in the quite extensive body of work based on police student surveys (including, but not restricted to Annell, Lindfors, & Sverke, 2015;Bäck, 2015;Fekjaer, 2014;Lagestad, 2013;Petersson, 2015), surveys of police officers (e.g. Ask, 2010;Burke & Mikkelsen, 2006;Dean, Fahsing, & Gottschalk, 2006;Ekenvall, 2003;Hansson, Hurtig, Lauritz, & Padyab, 2017;Hellesø-Knutsen, 2013) and some studies based on population surveys (Holmberg, 2005;Thomassen, 2017;Thomassen, Strype, & Egge, 2014).…”
Section: Current Methods In Police Researchmentioning
confidence: 91%
“…The education level of Indians exceeded that of the majority population (Fekjaer 2007). The Vietnamese refugees had low levels of education (Bringsrud 2014), whereas the Iranian refugees, especially women, had high average education levels (Blom and Henriksen 2008). Immigrants are in general, however, overrepresented in the lower social strata in Norwegian society, and there is a significant ethnic wage gap (Statistics Norway 2017b), which implies that a larger proportion of second-generation immigrants grow up in working-class families compared with the ethnic majority.…”
Section: The Norwegian Contextmentioning
confidence: 99%